Organizational Communication Patterns In Disaster Management - Fitriani Fitriani (Department of State Administration - Musamus University, 2018)
The research objective is to find out the right communication patterns used in disaster management by organizations. This research uses descriptive qualitative research methods with literate data collection techniques. The results of this study indicate that organizations can use star communication patterns and chain communication patterns, Star communication patterns are used to communicate in general, where superiors directly communicate with subordinates and subordinates directly communicate to superiors without intermediaries from others. For the chain pattern in the organization is used to provide information that is announcement from one division to all employees that must be submitted through the division. Communication from superiors to subordinates in the form of work or task instructions. Communication from subordinates to superiors is communication in the form of work reports, information about disasters and advice.